2007
DOI: 10.1523/jneurosci.4690-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neural Variability, Detection Thresholds, and Information Transmission in the Vestibular System

Abstract: A fundamental issue in neural coding is the role of spike timing variation in information transmission of sensory stimuli. Vestibular afferents are particularly well suited to study this issue because they are classified as either regular or irregular based on resting discharge variability as well as morphology. Here, we compared the responses of each afferent class to sinusoidal and random head rotations using both information theoretic and gain measures. Information theoretic measures demonstrated that regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
245
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(268 citation statements)
references
References 72 publications
(110 reference statements)
19
245
4
Order By: Relevance
“…Moreover, both models have been shown to be qualitatively equivalent for the most part (Liu and Wang 2001), although a recent study has pointed out some differences in terms of spike frequency adaptation . The leaky integrate-and-fire model with dynamic threshold can furthermore successfully reproduce experimental data from the electroreceptors of weakly electric fish (Chacron et al 2000(Chacron et al , 2004aBrandman and Nelson 2002;Chacron 2006;Savard et al 2011) as well as vestibular afferents (Sadeghi et al 2007). Recent experimental evidence shows that threshold fatigue is also present in electrosensory pyramidal neurons ).…”
Section: Mechanisms That Give Rise To a Single Negative Isi Correlatimentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, both models have been shown to be qualitatively equivalent for the most part (Liu and Wang 2001), although a recent study has pointed out some differences in terms of spike frequency adaptation . The leaky integrate-and-fire model with dynamic threshold can furthermore successfully reproduce experimental data from the electroreceptors of weakly electric fish (Chacron et al 2000(Chacron et al , 2004aBrandman and Nelson 2002;Chacron 2006;Savard et al 2011) as well as vestibular afferents (Sadeghi et al 2007). Recent experimental evidence shows that threshold fatigue is also present in electrosensory pyramidal neurons ).…”
Section: Mechanisms That Give Rise To a Single Negative Isi Correlatimentioning
confidence: 88%
“…This assumes that the stimulus intensity is small so that the perturbations brought about by the stimulus are small in magnitude and will thus scale linearly with the stimulus intensity. Experimental results have shown that this is the case in both electroreceptor (Chacron et al 2005b) and vestibular afferents (Sadeghi et al 2007), provided that the stimulus intensity is not too high (but see (Savard et al 2011)). Investigators have therefore focused on understanding how ISI correlations can alter the power spectrum of the baseline activity.…”
Section: Effects Of Isi Correlations On Information Transmission: Noimentioning
confidence: 99%
“…As a consequence, Oswald et al (2007) showed that an ideal observer could distinguish different stimulus amplitudes using the amount of time between two consecutive spikes within a burst. As the value of the burst ISI was typically <10 ms and the time scales associated with the stimulus were in that study were greater than 16 ms, they showed that information about the stimulus is contained in the structure of the burst at time scales that are smaller than those contained in the stimulus, which constitutes a temporal code by definition (Theunissen and Miller 1995;Dayan and Abbott 2001;Jones et al 2004;Sadeghi et al 2007). Our previous results obtained in vivo did not find such strong correlations between burst and stimulus attributes (Avila Akerberg et al 2010).…”
Section: Do Bursts Contain Information About Sensory Stimuli In Theirmentioning
confidence: 91%
“…Previous theoretical studies have investigated the consequences of variability in the baseline activity on information transmission (Chacron et al 2004b;Chacron et al 2005b, d;Lindner et al 2005). In particular, the power spectrum of the baseline activity can be seen as a "noise spectrum" and determines the amount of noise at each frequency during stimulation (Sadeghi et al 2007). As such, a more variable baseline activity will give rise to greater noise power and thus, a lower signal-to-noise ratio and information transmission.…”
Section: Increasing Variability Decreases Correlations Between Burstmentioning
confidence: 99%
“…Equivalently, this implies that information is contained in the response at time scales that are shorter than those contained in the stimulus, which is by definition a temporal code (Theunissen and Miller, 1995;Dayan and Abbott, 2001;Jones et al, 2004;Sadeghi et al, 2007).…”
Section: Modeling Electroreceptor Afferent Responses To Am Stimulimentioning
confidence: 99%